POLA PEMUKIMAN DALAM ARKEOLOGI: REKONSTRUKSI EKOLOGI, KEBUDAYAAN, DAN STRUKTUR MASYARAKAT - nfn Hasanuddin (WalennaE, 2001)
Settlement pattern concept appears in 1940s in America, and in these last few years has already been implemented in many researches in Indonesia. What is the real settlement pattern in archaeology and how does it scope? Willey, Vogt, Rouse and Mundardjito's concepts which are emphasizing in pattern, distribution, and its relations are interesting to be attended to understand and to reconstruct the past ecology, culture and social structure.